An Alternative Regularization Method for Equilibrium Problems and Fixed Point of Nonexpansive Mappings - Shuo Sun (Journal of Applied Mathematics)
We introduce a new regularization iterative algorithm for equilibrium and fixed point problems of nonexpansive mapping. Then, we prove a strong convergence theorem for nonexpansive mappings to solve a unique solution of the variational inequality and the unique sunny nonexpansive retraction. Our results extend beyond the results of S. Takahashi and W. Takahashi (2007), and many others.